BARISTA: DIGITAL MATERIALS FOR ENHANCING DANCE ARTS STUDENTS’ ENGLISH PRESENTATION SKILLS - Basra, Sri Meiweni; Merdila Nuril Fahmi; Fadli Ilham; Jessica Trinanda; Fathurrahman Hafid (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study explores the role of BARISTA (Bahasa Inggris untuk Presentasi Konsep Pertunjukan Tari), a digital learning resource developed to enhance the English presentation skills of Dance Arts students at the Indonesian Institute of the Arts Padangpanjang. It focuses on three aspects: the challenges students face in speaking English, their perspectives on the BARISTA materials, and insights into the integration of tailored digital media in English for Specific Purposes (ESP). A descriptive qualitative method was employed with 15 undergraduate students, using classroom observations, student reflections, and informal interviews as data sources. Findings indicate that students struggle with limited vocabulary, grammar complexity, and lack of supportive English-speaking environments, which affect their confidence in spontaneous communication. However, students evaluated BARISTA positively, describing it as engaging, clear, and highly relevant to their academic needs. The combination of video tutorials and a flip guidebook enhanced concentration, curiosity, and motivation while offering discipline-specific vocabulary and communicative support for presenting dance concepts. The study highlights that tailored digital media fosters improvements in cognitive, motivational, and affective dimensions of learning. These outcomes align with ESP principles underscoring the effectiveness of integrating contextualized digital tools into language instruction. It is recommended that language and arts educators collaborate in adopting such resources, and that institutions provide broader support to embed ESP materials within curricula, preparing students to communicate their cultural heritage confidently on international platforms.